THE DEVELOPMENT INSTRUMENT OF PROBLEM BASED INSTRUCTION ON STATISTICS SUBJECT IN CLASS OF SMP - Buhaerah, Buhaerah (Universitas Negeri Makassar, 2013)
The research question is how to develop instruments problem based intruction of statistics subject which fulfill the criteria of valid, practical, and effective. The objective of the research is to produce instruments of problem based instruction on statistics subject which fulfill the criteria of valid, practical, and effective. This research is a developmental research. The intended product of the research is the Instruments of problem based intruction which are valid, practical, and effective. The product consisted of five components: the lesson plan, student’s book, student’s work sheets, teacher’s guidance book, and the learning result test. The instruments employed were the validation sheet instrument, observation sheet on the application of the instrument, and the instrument of learning result test. The development process of teaching instruments employed four-D model which consisted of four stages: (a) The defining stage which studied pre and post analysis, (2) student’s analysis, (3) material analysis, (4) the formulation of teaching objective which identify, specify, and arrange the concept systematically to organize the teaching material; (b) The designing stage which convered problem based intruction teaching plan with the conducted activities: (1) the test arrangement, (2) media selection, (3) format selection, (4) pre-designing of prototype I; (c) The developing stage with the activities: (1) the content validation conducted by the experts and practitioners in education (prototype II), (2) simulation and test of legibility, (3) conducting field experiment (prototype III) of the teaching instruments which were organized; and (d) the disseminating stage, which the limited socialization and the dissemination of teaching instruments were conducted to abtain constructive feedback from the practitioners of mathematics educations (final prototype). The experiment of the research was conducted once. It was conducted in class IX4 of SMP Negeri 3 Parepare. The result of the experiments: (1) the problem-based teaching instruments were already practical, however suggestions from the observans should be taken into consideration to improve the practicality of the teaching instruments, (2) the problem-based teaching instruments were already effective because it fulfilled three out of four indicators effectiveness, those were the learning result classical compliteness was achieved, teachers ability in managing the teaching learning was in high category and student’s responses were in positive category. By following those development stages, the problem-based learning instruments which fulfilled the criteria of valid, practical, and effective, were obtained Based on the implication of the research, it was suggested that (1) researchers who are interested in developing further research are expected to consider the limitation of the research to complete the result of this research and (2) the development of such learning instrument ought to be conducted to other subject to make student’s interested, enjoy, and active, be able to construct their knowledge in learning mathematics.